Regional settlement infrastructure and currency internationalization: The case of Asia and the renminbi - Changyong Rhee; Lea Sumulong (Asian Development Bank Institute (ADBI), 2014)
The squeeze in United States dollar liquidity that emerged with the global financial crisis highlighted the risks inherent in the current global financial system. Asia was adversely affected by the crisis not only because of its dependence on trade, but also because of its heavy reliance on the US dollar for regional and international transactions. As Asia's role in the global economy continues to expand, its dependence on the US dollar is bound to increase, raising further its vulnerability to future liquidity shocks. The use of regional currencies for bilateral trade settlement could reduce such vulnerability. As demonstrated by the renminbi trade settlement scheme piloted between the People's Republic of China; Hong Kong, China; and Macao, China, the existence of appropriate financial infrastructure could reduce the relatively larger costs of bilateral currency transactions compared with triangular transactions through the United States dollar. As most central banks are securities depositories of government bonds, combining trade settlement with government bond securities settlement could also have large synergy effects without substantial extra costs. This proposal does not require full liberalization of the capital account or full deregulation of capital markets, and is more politically feasible in transition. As such, extending the trade settlement scheme to the rest of Asia and appending a government bond payment and securities settlement system could be a practical solution to international monetary system reform and the diversification of settlement currencies.
Keywords: F33; F34; F42; 330; global financial crisis; international monetary system; renminbi internationalization; renminbi trade settlement; government bond payment and settlement; Internationales Währungssystem; Wechselkurspolitik; Renminbi; Asien